The People United? : Australian solidarity with Latin America since Allende - Austin, Robert (2012)
Australia’s vibrant but largely-invisible history of international solidarity dates from the time of colonial occupation in 1788. The first documented experiences featured Irish political prisoners deported as slave labour to Australia—“convicts” in colonial terminology—linking up with Aboriginal warriors fighting native extermination to wage a guerrilla war against their common enemy, the land-hungry English colonialists. Three iconic episodes capture this popular rebellious tradition: the Eureka Stockade, a miners’ uprising at Ballarat against the colonial government in 1854 , which flew the Southern Cross flag later adopted by construction unions, the republican movement and solidarity brigades to the Cuban Revolution; popular rejection of military conscription and refusal to fight for British imperialism in World War I; and Australia’s provision of one of the largest per capita contingents in the International Brigade which fought for the Republic against fascism during the Spanish Civil War (1936-1939). Against that background, the transition to solidarity struggles fought at the political rather than military level came readily to the Left, once the Arctic winds of military dictatorship began to freeze the decolonization and socialist projects in much of Latin America, in the wake of US-sponsored military coups in Guatemala (1954), Brazil (1964), and Chile (1973).